2011
DOI: 10.4103/2229-4708.93390
|View full text |Cite
|
Sign up to set email alerts
|

High performance liquid chromatographic method development for simultaneous analysis of doxofylline and montelukast sodium in a combined form

Abstract: Aim:Some literatures revealed that the high performance liquid chromatography (HPLC) method for single component or multicomponent analysis of montelukast sodium with other drugs. However, these methods deals with time consuming, so it is necessary to develop a cost-effective and less time consuming method for the estimation of doxofylline and montelukast sodium in combined pharmaceutical formulation.Materials and Methods:The separation was performed on an inertsil C8 (5 μm, 4.6 × 250 mm) column in isocratic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…And software suggested the optimized ratio of the mobile phase is (80:20), which is closer to our actual experimental ratio, i.e. (85:15) [35][36][37] . Experimental data obtained for both trials approximately matches the data provided by DOE software which shows the authenticity of the chromatographic condition.…”
Section: Discussionsupporting
confidence: 76%
“…And software suggested the optimized ratio of the mobile phase is (80:20), which is closer to our actual experimental ratio, i.e. (85:15) [35][36][37] . Experimental data obtained for both trials approximately matches the data provided by DOE software which shows the authenticity of the chromatographic condition.…”
Section: Discussionsupporting
confidence: 76%
“…Even though there are official methods for analyzing montelukast sodium in pharmacopoeias or research articles, we have an expedient in-house procedure that we employ for this study (Singh et al, 2010;Rashmitha et al, 2010;United States Pharmacopeial, 2023). The analytical method of montelukast sodium using HPLC was validated according to the ICH guidelines (Eldin et al, 2011;Singh et al, 2010;Ethiraj et al, 2011). Figure 2 displays the chromatogram of montelukast sodium in the standard solution, tablet sample, and excipient signal.…”
Section: Analytical Validation Resultsmentioning
confidence: 99%
“…According to ICH guidelines, the proposed HPLC method by Revathi et al. was validated and good linearity, accuracy, repeatability, and precision were found [41].…”
Section: Analytical Methods Used To Estimate Montelukast Sodiummentioning
confidence: 99%
“…The selected chromatographic condition was found to separate doxofylline and MONTE accordingly (retention times: 3.4 and 5.5 min, respectively), and percent recoveries ranged from 98.1 to 101.9%, respectively. According to ICH guidelines, the proposed HPLC method by Revathi et al was validated and good linearity, accuracy, repeatability, and precision were found [41].…”
Section: High-performance Liquid Chromatography (Hplc)mentioning
confidence: 99%